Hambatan Peran Masyarakat Dalam Pengembangan Kampung Tanggui Sebagai Kampung Wisata Di Kota Banjarmasin - Sabrina Rosyidah; Sigit Ruswinarsih; Rahmat Nur (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2023)
Kampung Tanggui is located in Kuin Cerucuk Village, Banjarmasin City. Tanggui is a round hat in the shape of a hat used by the community as a head protector from activities under the sun, especiallyOriver community activities. The raw material for tanggui comes from nipa palm forests which can beOfoundPon the banksOof rivers, especially rivers which are still affected by sea tides. The method used in this study is aOqualitativeomethod. TheOdata source wasOselected by snowball sampling technique. DataOcollection wasOcarried out byOobservation, interview and documentationOtechniques. The data analysisOtechnique used is dataOreduction technique, data presentation,OandOconclusionOdrawing. Testing the validityOof theOdata wasOcarried0outPby sourceOtriangulation, technical triangulation and time triangulation. TheOresults of thisOstudy indicate that the form ofOthe community's role as tourism executor in the development of Kampung Tanggui as a tourist village in Banjarmasin City is divided into three roles. (1) The role in this decision-making is in the form of a free community of opinion to convey criticism and suggestions for progress in the development of Kampung Tanggui. (2) RoleOin improvingOthe quality of tourism products. The community plays a role in mutual cooperation activities for the convenience of tourist destinations and efforts to increase sales of tourism products. (3) Role in sharing financial benefits. The distribution of these financial benefits is in the form of economic benefits felt by the communityOand the availability of jobs in the Kampung Tanggui tourist area.